Influence of laser-generated surface micro-structuring on the intrinsically bonded hybrid system CFRP-EN AW 6082-T6 on its corrosion properties - Delp, Alexander; Freund, Jonathan; Wu, Shuang; Scholz, Ronja; Löbbecke, Miriam; Haubrich, Jan; Tröster, Thomas; Walther, Frank (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Examining the Neural Processes of Valence-Dependent Feedback Processing and Practice-Related Changes in Extensive Motor Learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Surprising effects of frontal neural correlates of augmented feedback-processing in extensive motor learning - Margraf, Linda; Krause, Daniel; Weigelt, Matthias

Professionswissen von angehenden Sportlehrkräften zur Gestaltung ei-nes bewegungsorientierten Schulalltags. Eine empirische Untersuchung im Bereich des Professionswissens von Lehrpersonen. - Satzinger, Nicole
Forschungsarbeiten zum Professionswissen von Sportlehrer*innen beschränkt sich weitgehend auf den Sportunterricht. Dem außerunterrichtlichen Schulsport wurde bisher wenig Aufmerksamkeit geschenkt. Hier setzt die vorliegende Arbeit an, die sich auf das Professionswissen von Sportlehrer*innen zur Gestaltung eines bewegungsorientierten Schulalltags konzentriert. Als theoretische Rahmung liegen den Überlegungen das Kompetenzmodell von Baumert und Kunter (2011) und das Zahnradmodell der "Bewegten Schule" von Städler (2016) zugrunde. Die empirische Untersuchung basiert auf einem dreistufigen Vorgehen. Zuerst wurde im Rahmen von fünf Fokusgruppeninterviews mit Expert*innen die aus Praxissicht relevanten Wissensfacetten des Professionswissens zur Gestaltung eines bewegungsorientierten Schulalltags erhoben. Die Auswertung erfolgte auf Basis der qualitativen Inhaltsanalyse nach Mayring (2015). Darauf aufbauend wurden die Facetten in einer Fragebogenerhebung von Expert*innen hinsichtlich ihrer jeweiligen Relevanz bewertet, anschließend wurden die Ergebnisse bilanzierend zusammengeführt. Es konnten 46 Wissensfacetten des Professionswissens identifiziert werden, die in 11 übergreifenden Kategorien geclustert wurden. Die Bereiche des Professionswissens nach Baumert und Kunter (2011) werden vollständig abgebildet und eine Zuordnung dem Zahnradmodell von Städler (2016) fand statt. Ein Professionswissen im Bereich Organisation und Beratung scheint relevant zur Gestaltung eines bewegungsorientierten Schulalltags zu sein. Die Erkenntnisse können als Ansatzpunkt für Forschungsarbeiten sowie für die universitäre Ausbildung dienen.
Keywords: Professionswissen; Sportlehrerausbildung

Augmented feedback and motor automatization - Krause, Daniel; Margraf, Linda; Weigelt, Matthias; Blischke, Klaus

A longitudinal analysis of reciprocal relationships between actual and perceived motor competencies and physical self-concept in primary-school age children - Strotmeyer, Anne; Herrmann, Christian; Kehne, Miriam (Psychology of Sport and Exercise)
Physical self-concept (PSC) and motor competencies are important factors in view of the development of a physically active lifestyle. There are research gaps regarding longitudinal studies of these relationships. This article presents findings of a longitudinal study (n = 200; 58% girls, M = 8.84 ± 0.63 years) at three primary schools. The aim of this study was to analyze the relationship between actual motor competencies (AMC) and perceived motor competencies (PMC) and PSC. Therefore, manifest path models in cross-lagged design were performed. Results show that correlations between PMC and AMC increased over time and were stronger in object control than in locomotor. Effects of AMC on PSC were more strongly mediated by PMC in object control than in locomotor. To promote physical activity, developing strategies should be aimed at the acquisition of AMC, particularly in object control, and PMC, especially in locomotor, during childhood.
Keywords: Applied Psychology

Gesundheit und Stress im Studium - Bedeutung gesundheitsrelevanter Lebensstile - Waltert, Carolin

Die ausgekugelte Schulter im Kanusport. Behandlung und Vorbeugen - Bauer, A.; Buhmann, H. W.; Güldenpenning, Iris (Kanusport)

Produktionskosten von Täuschungshandlungen im Sport: Der Einfluss von Übung auf die Durchführung von Blicktäuschungen im Basketball - Böer, Nils Tobias; Weigelt, Matthias; Schütz, Christoph; Güldenpenning, Iris (Ein Gehirn, viel Bewegung – Variabilität und Plastizität über die Lebensspanne. Abstractband der 54. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Producing deceptive actions in sports: The costs of generating head fakes in basketball - Böer, Nils Tobias; Güldenpenning, Iris; Kunde, Wilfried; Weigelt, Matthias (Abstracts of the 64th Conference of Experimental Psychologists (TeaP))

Kognitive Grundlagen von Täuschungshandlungen im Sport - Weigelt, Matthias; Güldenpenning, Iris (Kognition und Motorik: Sportpsychologische Grundlagen und Anwendungen im Sport)

Citizen Social Science in Germany—cooperation beyond invited and uninvited participation - Göbel, Claudia; Mauermeister, Sylvi; Henke, Justus (Humanities and Social Sciences Communications)
Abstract This article presents an overview of characteristics of Citizen Social Science (CSS) in Germany. CSS is defined as scientific research in the humanities and social sciences, carried out in cooperation between professional and non-professional researchers. The study draws on an online survey and semi-structured interviews with project coordinators and co-researchers. It finds that participatory research activities in the humanities and social sciences are very diverse in their disciplinary traditions and organisational settings. Key features of CSS activities initiated inside as well as outside academic institutions are analysed to understand patterns of participation and cooperation. The results show that CSS activities are frequently realised in heterogeneous consortia of academic and non-academic partners. These consortia influence interactions between professional and non-professional researchers. To investigate these observations further, the article extends the analytical gaze from participation of individual volunteers to various forms of cooperation in consortia. This shift in attention brings to sight additional actors and activities that are usually not, or only marginally, considered in discussions about C(S)S. Staff of civil society organisations, municipalities, schools or cross-sectoral initiatives as well as university students are involved in making CSS work. In addition to research tasks, CSS rests on science communication, project management and intermediation activities. This extended perspective captures more diverse constellations of knowledge production in participatory research in the social sciences and humanities than the common focus on participation. In this way, the article aims to lay the groundwork for understanding the functioning of CSS beyond aspects described by the concept of invited and uninvited participation. It shows that CSS activities are not limited to capacitating lay people for participation in science. A more adequate description is that such projects are concerned with facilitating cooperation with co-researchers and other partners in consortia inside and outside of academia. On this basis, the article introduces the notion of cooperation capacity as a heuristic device to propose new prompts for research on CSS as well as for supporting CSS practice.
Keywords: General Economics; Econometrics and Finance; General Psychology; General Social Sciences; General Arts and Humanities; General Business; Management and Accounting

Eingeschrieben und Geblieben. Herkunftsgruppenspeziﬁsche Bedingungen des Studienverbleibs nach der Studieneingangsphase an Universitäten. - Mauermeister, Sylvi
Hochschulische Bildungsverläufe und -erfolge sind in Deutschland anhaltend maßgeblich von der sozialen Herkunft beeinflusst. Gleichzeitig bestehen Anforderungen an moderne Gesellschaften, Unterschiede in den bildungsbezogenen Chancen abzuschaffen, die nicht aus Leistungsunterschieden, sondern aus der Zugehörigkeit zu bestimmten sozialen Gruppen resultieren. Auch angesichts der hohen Bedeutung der Studieneingangsphase für den Studienerfolg stellt sich die Frage, wie sich Unterschiede in den ökonomischen und kulturellen Ressourcen der Herkunftsfamilie auf den Verlauf der Studieneingangsphase auswirken. Welche Unterschiede zeigen sich in den Bedingungen des Studienverbleibs, der Ausstattung mit studienverbleibsrelevanten Ressourcen und dem Umgang mit Problemen? Die Untersuchung zeigt vor allem zweierlei: Zum einen sind die Schwierigkeiten mit den universitären und fachspezifischen Bedingungen, die bereits nach dem ersten Studiensemester sichtbar werden, stark abhängig von der Fächergruppe, in der studiert wird. Zum anderen ist für das Gelingen der Studieneingangsphase das kulturelle Kapital der Herkunftsfamilie von größerer Bedeutung als das ökonomische Kapital. Die Ergebnisse sind gleichermaßen für die Bildungs- wie die Ungleichheitsforschung relevant und erlauben es, Handlungsoptionen zur Gestaltung der Studieneingangsphase abzuleiten.

Paralleluniversen des Wissenschaftsmanagements: Ein Vergleich zwischen Hochschulen und außeruniversitären Forschungseinrichtungen. - Schneider, Sebastian; Mauermeister, Sylvi; Aust, Robert; Henke, Justus

„LauRa - In der Lehramtsausbildung Reflexionskompetenz analysieren“ : Untersuchungen zum Verhältnis von Theorie, Praxis und Reflexion im Rahmen der Professionalisierung angehender Lehrpersonen - Meier, Jana

Experimental Investigation of the Influence of different Bond Tool Grooves on the Bond Quality for Ultrasonic Thick Wire Bonding - Hagedorn, Oliver Ernst Caspar; Broll, Marian; Kirsch, Olaf; Hemsel, Tobias; Sextro, Walter (CIPS 2022 - 12th International Conference on Integrated Power Electronics Systems)
To achieve optimum bond results at ultrasonic bonding thick copper wire on sensitive components is quite challenging. Bearing in mind that high normal force and ultrasonic power are needed for bond quality but as well increase stress and finally failure risk of the substrate, methods should be found to achieve high bond quality even at lower bond parameters. Therefore, bond experiments with different bond tool grove geometries have been conducted for copper and aluminum wire on direct copper bonded (DCB) substrates to investigate the impact of geometric parameters on bond formation and bond quality. The wire material depending impact of geometry changes on the bond formation and deformation was quantified. Additionally, a bonding parameter design of experiments (DOE) has been conducted for the reference and the most promising groove geometry. Higher shear values were achieved at reduced vertical tool displacement for most bonding parameter combinations, compared to the reference tool. This behavior allows for reducing ultrasonic power to obtain equal shear values; consequently, mechanical stresses in the interface decrease. This could potentially reduce the risk of chip damage and thus yield loss.

Unter Druck. Kommunikationen, Medien und Kulturen als Seismographen gesellschaftlicher Transformationen. - Jacke, Christoph (Druckwellen)

On the applicability of time series features as health indicators for technical systems operating under varying conditions - Aimiyekagbon, Osarenren Kennedy; Bender, Amelie; Sextro, Walter (Condition Monitor)

Experimental Investigation of Multidimensional Ultrasonic Heavy Wire Bonding - Scheidemann, Claus; Kirsch, Olaf; Hemsel, Tobias; Sextro, Walter (2022 IEEE 9th Electronics System-Integration Technology Conference (ESTC))
ue to the constantly growing energy demand of power electronics and the need to reduce the size of electronic components like power modules for e-mobility, new challenges arise for ultrasonic wire bonding: the electrical connection must endure higher thermal and mechanical stress while the connecting partners become more sensitive or require more energy to get bonded. Past investigations have shown already that multi-dimensional ultrasonic bonding and welding yield the same or even better bond quality while reducing the load on the components. This contribution is intended to show whether multidi-mensional thick wire bonding is a promising concept to over-come the new challenges. The focus is on experimental investi-gations of different bond tool trajectories in ultrasonic wire bonding of aluminum and copper wire on DCB's and chips. The bond quality is analyzed by shear tests, microsections and, in the case of aluminum bonding, by a new machine learning method for an objective automated evaluation of the sheared area.

Sport Emotion Questionnaire - Ein valides Messinstrument für den Freizeit- und Gesundheitssport? - Thorenz, Kristin; Weigelt, Matthias (Poly-Pill Bewegung. Chancen, Risiken und Nebenwirkungen)